Challenges in studying the toxicity of particulate air pollution on the respiratory system - Takano, Ana Paula Cremasco; Closs, José Guilherme Veras; Fajersztajn, Laís; Veras, Mariana Matera (Frontiers in Environmental Engineering, 2025)
Air pollution, particularly particulate matter (PM) from vehicular emissions, poses significant risks to human health, with evidence linking it to respiratory and other systemic effects. This review provides a brief historical overview of air pollution to understand the evolution of pollution sources and their health effects. Key challenges in PM exposure assessment are explored, particularly the difficulty of accurately estimating exposure and inhaled dose. The review also addresses PM deposition in the lungs, its elimination, and its impact on both local and systemic health. The role of the lung microenvironment, specifically the extracellular matrix, is critical to understanding PM-induced tissue damage and its broader implications. Despite research advancements, uncertainties persist regarding PM toxicity mechanisms, its role in chronic diseases, and the development of reliable biomarkers. This review emphasizes the need for a multidisciplinary approach to address these health challenges, utilizing technological innovations to improve exposure assessment and better understand PM’s toxicological effects. Global collaboration is essential to mitigate health risks and protect public health.